LEGAL PROTECTION OF MARRIAGES BETWEEN EMPLOYEES OF ONE COMPANY BASED ON CONSTITUTIONAL COURT RULING NO. 13/PUUXV/2017 AND LAW NUMBER 13 OF 2003 - Mofea, Sukhebi (Jurnal Pembaharuan Hukum, 2023)
In managing its employees, every company has several policies, such as regulating employees who cannot marry within the same company for reasons of reducing conflict, subjectivity, corruption and nepotism. This writing aims to find out and analyze the legal protection of marriage between workers in a company which is analyzed using legal studies. The research method used is normative legal research with a statutory approach and uses a library method that is analyzed juridically. The results of the research are a form of legal protection for husband and wife who work in the same company and legal protection for workers or laborers, namely protection of the right to terminate employment relations, workers/laborers have the right to receive compensation from the employer in the event of layoffs, compensation consisting of severance pay, money long service awards and compensation money for workers' rights.